Tingkat Partisipasi Kelompok Tani “Rukun Tani” pada Pemeliharaan Jaringan Irigasi di Dusun Waru, Desa Warungering, Kecamatan Kedung – Pring, Kabupaten Lamongan - SALIMI, MUHAMMAD CHULIL; BUDIASA, I WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
The Participation Rate of Farmer Groups  of Rukun Tani  in the Maintenance of Irrigation Networks in Waru Hamlet,  Village of   Warungering,  Sub-District of  Kedung-Pring,  Regency of  Lamongan The tertiary irrigation network in Waru Hamlet was damaged due to poor maintenance of facilities and infrastructure on the irrigation canal. This indicates that the participation of the Rukun Tani Farmers Group is not good in maintaining irrigation networks. The purpose of this study is to determine the rate of participation by reviewing the implementation of operations, maintenance and financing carried out by the Rukun Tani Farmer Group. Respondents in this study consisted of 44 members of the Rukun Tani Farmers Group. Analysis using qualitative descriptive methods.  The results of this study indicate that the rate of participation of members of the Rukun Tani farmer group is in the low category, as measured by the implementation of operations, maintenance and financing that get a high category so that the processed results get a low category. The Rukun Tani farmer group considers that by paying irrigation fees, it has carried out its contribution in maintaining the irrigation network. The Rukun Tani farmer group should have participated in the operation and maintenance of the irrigation network, which was coordinated by the Village HIPPA officer.